(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In this article analyzes programs that allow you to detect, track and control the flow of passengers at the station through a Wi-Fi device. We also studied wireless IP cameras connected to a Wi-Fi device, their types and additional features.